IMPLEMENTATION OF ADDITIVE RATIO ASSESSMENT (ARAS) METHOD ON DECISION SUPPORT SYSTEM FOR RECIPIENT OF INHABITABLE HOUSE - Budy Satria (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2020)
In Air Jamban distric office, there are problems for the distribution of housing assistance, one of which is that it is very difficult for related parties to provide assistance to prospective recipients who are in dire need and on target. The assessment system for prospective beneficiaries for inhabitable house is still subjective. Therefore, this study will discuss a decision support system in order to help the Air Jamban village in determining the beneficiaries of livable housing based on 8 predetermined criteria, namely fuel for cooking (C1), home status (C2), number of children (C3) , income (C4), house floor type (C5), house roof type (C6), wall type (C7) and house area (C8) using the Additive Ratio Assessment (ARAS) method and using 10 alternative data. The results of the ARAS method calculation there are 6 names that can be recommended, the highest (Ki) value is 0.101034482, 0.099586176, 0.097412263, 0.093309699, 0.091426639 and 0.090745596